Capacete na cabeça, pra quê? um estudo sobre o Parque Nacional Cavernas do Peruaçu na perspectiva dos guias locais - Miranda, Elisangela Santos de (2017)
This research starts from a debate about a possible conflict of interest between traditional members of the community and need to protect natural resources in conservation units open to visitors. In these territories, the concept of preservation favours social transformations that have as a backdrop the landholding issues, as well as tourism expectations. We took as case study the implantation of the 'Cavernas do Peruaçu National Park', through the professional practice of the local tour guides. We aimed to understand the relationship between the local population with the park from the tour guide's view. The research took place as soon as the park started to receive visitors, we have elaborated a plan conducted by some of the tour guides which were also part of the local community. To achieve the objective of this study, interviews were conducted with the local tour guides to understand how they position themselves in relation to tourism and the environmental conservation, and how they present the park to the visitors. During all visits to the park, we read some of the official local documents, we created a diary to record all notes as well as engaging in conversations with the tour guides. We focused on how to understand the language in the social aspect, we have also focused on natural language. In other words, how discursive practices produce cultural meanings and how people position themselves in their everyday relations